2018
DOI: 10.3389/fncel.2018.00243
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics Control Microglia Plasticity

Abstract: Microglia, resident immune cells of the central nervous system, fulfill multiple functions in the brain throughout life. These microglial functions range from participation in innate and adaptive immune responses, involvement in the development of the brain and its homeostasis maintenance, to contribution to degenerative, traumatic, and proliferative diseases; and take place in the developing, the aging, the healthy, or the diseased brain. Thus, an impressive level of cellular plasticity, appears as a requirem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
100
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(105 citation statements)
references
References 137 publications
3
100
2
Order By: Relevance
“…Although a handful of studies have suggested DNA methylation as a principal regulator of microglial activation 34 , little microglia-specific in vivo evidence is available to compare DNA methylation with concurrent changes in transcriptomic response. By coupling LPS administration with the cell type-specific Cx3cr1-NuTRAP model we are able to interrogate dynamic changes in DNA methylation in Cx3cr1 + (microglia) cells with their paired transcriptomic changes indicative of a pro-inflammatory response.…”
Section: Resultsmentioning
confidence: 99%
“…Although a handful of studies have suggested DNA methylation as a principal regulator of microglial activation 34 , little microglia-specific in vivo evidence is available to compare DNA methylation with concurrent changes in transcriptomic response. By coupling LPS administration with the cell type-specific Cx3cr1-NuTRAP model we are able to interrogate dynamic changes in DNA methylation in Cx3cr1 + (microglia) cells with their paired transcriptomic changes indicative of a pro-inflammatory response.…”
Section: Resultsmentioning
confidence: 99%
“…Neher and coworkers recently demonstrated that peripherally applied inflammatory stimuli which induce either acute immune training (e.g., single intraperitoneal injection of LPS) or tolerance (e.g., daily injections of low‐dose LPS on 4 consecutive days) in the brain lead to differential epigenetic reprogramming, associated with unique transcriptome profiles of microglia that persist for at least half a year (Wendeln et al , ). Epigenetic changes, including histone modifications or DNA methylation as well as microRNA expression, are important modifiers of gene expression, and have been involved in cell phenotype regulation and reprogramming and are therefore part of the mechanisms regulating cellular plasticity including microglia (Cheray & Joseph, ). These two types of immunological imprinting, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In the group of histone deacetylases (HDAC), expression of several genes was reduced: Hdac4, Hdac5, Hdac8, Hdac9, Hdac11, and Sirt5 ( Figure 3C). We analyzed also expression of genes related to epigenetic regulation, as emerging contributor to microglial plasticity ( Figure 3) [38]. Among tested genes, we focused on those involved in histone acetylation code.…”
Section: Resultsmentioning
confidence: 99%
“…to microglial plasticity ( Figure 3) [38]. Among tested genes, we focused on those involved in histone acetylation code.…”
Section: Resultsmentioning
confidence: 99%